DAMPAK PEMBELAJARAN DARING BAGI MENTAL SISWA SEKOLAH DASAR PADA MASA PANDEMI COVID-19 DI KELAS 3 SDIT MUTIARA INSAN - Afroh Nailil Hikmah; Indah Dahlia Putr (MISOOL: Jurnal Pendidikan Dasar, 2021)
This study aims to describe the impact of online learning on the mentality of elementary school students due to learning during the Covid-19 pandemic. This study uses qualitative research from 19 in Indonesia, since then the implementation of distance restrictions or social distancing has had an impact on education which ultimately face-to-face learning must be replaced with online learning. Currently learning to use mobile phones as a medium of learning. So that learning can be carried out anywhere. In the aspect of the success of this learning, it is quite less showing the expected success, the lack of success of this online learning occurs as a result of the impact of this learning.